Disain Irigasi Tetes Tipe Orifis Tanpa Pompa untuk Tanaman Slada Secara Hidroponik pada Rak-Rak Bertingkat - Muhammad Idrus (Jurusan Teknologi Pertanian, 2013)
The research was conducted at the Research Field of Lampung State Polytechnic, Bandar Lampung. The objectives of the research were (1) To design and construct the drip irrigation type orifice without pump for salad (Lactuca sativa L.) with hydrophonic system on cropshelf, and (2) To test irrigation efficiencies performance of the drip irrigation type orifice without pump. The result of the research showed that the drip irrigation type orifice without pump given distribution efficiency of water nutrition by 87.26%, water nutrition use efficeiency of 75.61%, and salad production average of 130.31 g/tanaman, and water nutrition productivity of 2.44 kg/m3. Salad production dan water nutrition productivity average by the drip irrigation type orifice without pump was higher compared to traditional water nutrition application. Keywords: The drip irrigation type orifice, water nutrition, efficiency, and Lactuca sativa L.